Effect of Laser Solution-Aging Process Parameters on the Hardness and Water Erosion Resistance of 17-4PH Stainless Steel - LI Yongke, XUE Xiang, LI Yong, WANG Xiaoen, LIU Gang, XIE Weiwei, WANG Mingyuan (Cailiao Baohu)
To address the issues of the last-stage blades of steam turbines being susceptible to pitting，water erosion and even fracture，surface laser solution-aging strengthening treatment was carried out on 17-4PH precipitation-hardened stainless steel using a rectangular laser spot with dimensions of 22.0 mm×4.9 mm and a focal length of 400 mm.The microstructure，hardness and water erosion resistance of the laser solutionaging strengthened layer under different process parameters were examined and analyzed using optical microscopy，scanning electron microscopy(SEM)，X-ray diffractometer (XRD)，microhardness tester and a water erosion test platform.Results showed that increasing the laser power or decreasing the scanning speed improved the hardness of the strengthened layer.In contrast，higher aging temperatures resulted in microstructural coarsening，which reduced the hardness of the strengthened layer.The experimental results indicated that the water erosion resistance of 17-4PH precipitation-hardened stainless steel after laser solution-aging strengthening was nearly 15 times higher than that of the 17-4PH steel substrate.